Gender Differences in Self-Employment in Finnish Regions - Hannu Tervo; Mika Haapanen (European Regional Science Association (ERSA), 2006)
Many studies show that gender predicts entries into self-employment – females are typically a minority of self-employed. Men also have a higher probability of remaining in business than women. In many countries, however, females represent the fastest growing segment among the self-employed. The reasons that lead women and men to enter self-employment can be very different, and may also differ between regions. A well-known but little understood fact is that rates of entrepreneurship exhibit pronounced and persistent variations across regions. The specification and understanding of regional entrepreneurial environments remains a complex issue. The aim of this paper is to throw some light on gender differences in entrepreneurship in Finland and its regions. Are there gender differences in self-employment rates, and if there are, for what reason? How do female entrepreneurs differ from male entrepreneurs with regard to predicted income, personal and household characteristics, assets, prior activity and industry? What is the husband's role in the household? Personal characteristics such as family size, marital status, and the presence and ages of children may play different role for women than they do for men. We intend to apply the structural probit model to female self-employment in order to test the hypothesis whether an individual is more likely to be self-employed the greater is the predicted relative income in self-employment. Our data set is based on a Longitudinal Census File and the Longitudinal Employment Statistics File constructed by Statistics Finland. Since 1987, the two basic files are updated annually in Finland. These two register-based data sets, together with some other registers, provide panel data on each resident of Finland, from which a 7 per cent random sample is taken for this study. The data set is very rich including hundreds and hundreds of variables for 1987-2002.
Keywords: 330